Comparison of Secondary Seal of White MTA, C&B Metabond and Cavit in Endodontically Treated Teeth Using Bacterial Penetration - AA - Khademi; N Hajihasani (Isfahan University of Medical Sciences, 2006)
Introduction: Coronal microleakage is the major cause of failure of root canal treatments. The purpose of this study was to evaluate the sealing ability of white MTA, C&B Metabond and cavit against coronal microleakage of Enterococcus faecalis for four months.Methods and Materials: Ninety extracted single-rooted human teeth were selected. Root canal instrument-tation and abturation with gutta-percha was performed. The teeth were randomly divided into four groups of 20 teeth each, plus two control groups consisting of 5 teeth. Three millimeters of gutta-parcha was removed from the coronal aspect of the root canals in the groups I, II, III and replaced with C&B Metabond, cavit and white MTA, respectively. The teeth in group IV did not receive an intraorifice barrier. The external surface of each root, except the apical region, was covered with two layers of nail varnish. All teeth were inserted in the designed system for this experiment. The whole system was sterilized and then transferred in a BHI culture. A fresh solution of E. faecials was injected in to the system every 3 days. The samples were evaluated daily for 120 days and the time of culture contamination with E. faecalis was registered in each case. Statistical tests of Variance and Duncan were used to analyze the results.Results: All the samples in positive control group were infected after 24 hours. None of the negative control samples were infected after 120 days. Group I (C&B Metabond) and group II (cavit) had no significant difference with group III (White MTA). But groups I, II were significantly different from group IV (without barrier). Group III wasn't significantly different with group IV.Conclusion: The obturated root canals that received a C&B Metabond or cavit orifice plug leaked significantly less than the obturated, unsealed group. Therefore, to prevent coronal microleakage this material can be recommended as a intraorifice barrier before restorative treatment is initiated